Language Styles Used in Secondate's Instagram Captions from 1 July to 27 December 2021 - Sella Berliana Utomo; Flora Debora Floris (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study aims to find out the language styles used by Secondate in the Instagram account captions. The writers did this study to find the language styles based on word choice in the Instagram account captions for the product Milky Gel Lip Tint. The writers used the theory of gaya bahasa berdasarkan pilihan kata or language styles based on word choice by Keraf (2006), which utilizes three indicators, namely sentence length, structure, and vocabulary. The writers also referred to the theory of syntax by Chaer (2007) and the theory of standard Indonesian by Prihantini (2015). The research was done using a qualitative approach. It was found that Secondate had many informal and conversational language styles and rarely used the formal language style in their Instagram captions